EVALUASI IMPLEMENTASI AKUNTANSI KEUANGAN DESA MULIOREJO KECAMATAN SUNGGAL KABUPATEN DELISERDANG - .HERTI DIANA HUTAPEA; Hendrik Elisa Sutejo Samosir (LP2MTBM MAKARIOZ, 2018)
This research aims to evaluate the implementation of rural financial accounting in Muliorejo village, how is the preparation and presentation of the MulioRejo village financial report in based on Permendagri No.113/2014 and the constraints in the process of preparing rural financial reports and solutions to overcome obstacles in the preparation of rural financial statements.The sample of this study was Muliorejo village, subdistrict Sunggal, Deli Serdang regency. Data collection techniques are carried out by observation, documentation. Interview and triangulation of data with descriptive analysis techniques year 2016.The results of this research that the implementation of rural financial accounting in Muliorejo Village had not yet fully carried out in the village of Muliorejo, starting from the recording phase, grouping phase, summary phase and reporting phase. In the Recording phase it has been done very well. In the grouping and summary phase it has not yet been done, because there are no journals or records that are only simple so that the recording of transaction evidence in the ledger does not yet exist and the balance sheet and working paper do not yet exist in the rural financial accounting. While this Reporting Stage has been done very well. Preparation and Presentation of rural Financial Statements Muliorejo Village is already quite good because it has complied with Permendagri No 113/2014 with consist of repoting of villange budget (APBDesa), General Cash Book, Bank Book, Tax Assistance Book, the realization of implementation of village budget report and the liquedfying the fixe nominal asset on villange assets report. And there are the constraints in the process of preparing rural financial reports is human resource capicity in the process of preparing the Muliorejo Village government report so as to improve the quality of Village, there is no Computerized System in the preparation of the 2016 Muliorejo Village government financial report and communication with all parties involved in the process of preparing the rural financial reports, the disbursement of village funds is late so that disrupts the process of preparing financial statements can run smoothly and precisely in the rural financial reporting.Based on the conclusion, it can be suggested that the Muliorejo Village bachelors go home to build a village to overcome the weakness of the human resource competencies of the village apparatus, preferably using a computerized system in the process of compiling rural government financial reports so that are better and more detailed and avoid mistakes and disbursement of village funds and recommend that disbursement of village funds not be late so as not to disrupt the process of preparing the village government financial statements.